2013
DOI: 10.1080/0361073x.2013.808109
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Limitations of the Mini-Mental State Examination Among Nondemented Older Adults: An Evaluation of Neurocognitive and Magnetic Resonance Imaging Correlates

Abstract: Overall, MMSE scores exhibited ceiling effects, poor test-retest reliability, limited sensitivity to subtle brain abnormalities, and a high rate of intrusion elsewhere in the neuropsychological battery. Individual MMSE items demonstrated poor construct validity. These qualities illustrate the serious limitations of the MMSE in detecting individual differences in cognitive function among healthy older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 17 publications
2
93
0
Order By: Relevance
“…15,16 Similarly, the method used to measure cognitive function, the MMSE, is a validated and widely used method of cognitive assessment, although it may have poor sensitivity for the detection of mild cognitive impairment, subtle changes in word recall, or impairment in executive function. 22,23 Our study has a number of limitations. First, because this is an observational study, we can only establish association and not causation, and the effect of residual confounding cannot be ruled out, as dietary habits tend to be lifelong and may be a proxy for other poor health behaviors that were either unknown or unmeasured.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 Similarly, the method used to measure cognitive function, the MMSE, is a validated and widely used method of cognitive assessment, although it may have poor sensitivity for the detection of mild cognitive impairment, subtle changes in word recall, or impairment in executive function. 22,23 Our study has a number of limitations. First, because this is an observational study, we can only establish association and not causation, and the effect of residual confounding cannot be ruled out, as dietary habits tend to be lifelong and may be a proxy for other poor health behaviors that were either unknown or unmeasured.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, according to Kim et al (2014) MMSE can be considered as a promising screening tool for mild cognitive impairment (MCI) when detailed neuropsychological tests are not feasible. On the other hand, Spencer et al (2013) using MMSE in the group of healthy older people showed its ceiling effects, poor test-retest reliability, and limited sensitivity to subtle brain abnormalities. It should be noted that awareness of the MMSE's limitations makes that it is used as screening assessment of cognition.…”
Section: Introductionmentioning
confidence: 92%
“…One important limitation of the latent class approach is that the number of identified classes may reflect floor or ceiling effects in available data [45]. The CPS and MMSE scores may lack appropriate sensitivity at lower levels of impairment to detect subtle changes [46,47], a limitation that has been discussed in previous research on heterogeneity in terminal decline [11]. That we were nevertheless able to observe terminal change in individuals with relatively low levels of impairment shows that floor effects were not particularly severe in the present study.…”
Section: Discussionmentioning
confidence: 99%